2016
DOI: 10.2147/ppa.s116198
|View full text |Cite
|
Sign up to set email alerts
|

A socioeconomic and behavioral survey of patients with difficult-to-control type 2 diabetes mellitus reveals an association between diabetic retinopathy and educational attainment

Abstract: BackgroundWe have recently reported that the attitude of patients toward risk could be a factor in the progression of diabetic complications. In general, risk preference is closely related to socioeconomic status (SES), which includes factors such as age, sex, income, and educational attainment.ObjectiveWe aimed to determine the effect of SES and behavioral propensity on the progress of diabetic complications in patients with type 2 diabetes mellitus (T2DM).MethodsWe conducted a survey of 238 patients with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
5
17
1
Order By: Relevance
“…Our finding that educational attainment was not shown to be associated with achieving glycaemic targets despite the strong association seen for IRSD highlights the complexity of studying the concept of SES and its relationship with chronic disease parameters. Our finding is in contrast to international studies suggesting that socioeconomic advantage measured at the individual level such as higher educational attainment [ 22 25 ], higher income [ 26 , 27 ] and higher residential stability [ 28 ], were associated with a greater likelihood of achieving HbA1c targets. However, there are many different measures and ways of defining SES, a concept that is made up of individual characteristics (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that educational attainment was not shown to be associated with achieving glycaemic targets despite the strong association seen for IRSD highlights the complexity of studying the concept of SES and its relationship with chronic disease parameters. Our finding is in contrast to international studies suggesting that socioeconomic advantage measured at the individual level such as higher educational attainment [ 22 25 ], higher income [ 26 , 27 ] and higher residential stability [ 28 ], were associated with a greater likelihood of achieving HbA1c targets. However, there are many different measures and ways of defining SES, a concept that is made up of individual characteristics (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were shown in a study in Thailand, where patients with low socio economic status were associated with complications of diabetes mellitus [20]. However, the patient individual income was found not to determine the diabetic complications in China where there was no association between patient's economic status and development of diabetic complications [21].…”
Section: Discussionsupporting
confidence: 82%
“…Studies conducted in Saudi Arabia [25], Korea [26] and Sudan [18] suggest that less educated or who had no formal education had a high probability of developing DR than who attained higher classes. Another finding from Tokyo suggests that lack of proper educational attainment was significantly associated with the progression of retinopathy [27]. The study done in Korean population revealed that illiterate patients had a high probability of developing diabetic complications like DR [28].…”
Section: Discussionmentioning
confidence: 98%